Un estrecho sendero para una vida mejor?: Sobre las causas y consecuencias del exito misionero que tienen las comunidades religiosas fundamentalistas y evangelicas en Bolivia - Ströbele-Gregor, Juliana (América indígena, 1992)
The author examines the growth of fundamentalist and evangelical groups in Bolivia, largely from the US, as part of the process of development that Bolivia's social system is experiencing, in particular, with the creation of an Aimara urban subculture in the city of La Paz. She looks into the reasons which lead to conversion, as well as the repercussions this has had on the political attitudes, and concludes that conversion in Bolivia to fundamentalist and evangelical religions is an adaptation strategy due to situations of profound social crisis. (Am.Indig.)